Translation of non-standard codon nucleotides reveals minimal requirements for codon-anticodon interactions. Issue 1 (December 2018) - Hoernes, Thomas; Faserl, Klaus; Juen, Michael; Kremser, Johannes; Gasser, Catherina; Fuchs, Elisabeth; Shi, Xinying; Siewert, Aaron; Lindner, Herbert; Kreutz, Christoph; Micura, Ronald; Joseph, Simpson; et al.
Abstract The precise interplay between the mRNA codon and the tRNA anticodon is crucial for ensuring efficient and accurate translation by the ribosome. The insertion of RNA nucleobase derivatives in the mRNA allowed us to modulate the stability of the codon-anticodon interaction in the decoding site of bacterial and eukaryotic ribosomes, allowing an in-depth analysis of codon recognition. We found the hydrogen bond between the N1 of purines and the N3 of pyrimidines to be sufficient for decoding of the first two codon nucleotides, whereas adequate stacking between the RNA bases is critical at the wobble position. Inosine, found in eukaryotic mRNAs, is an important example of destabilization of the codon-anticodon interaction. Whereas single inosines are efficiently translated, multiple inosines, e.g., in the serotonin receptor 5-HT2C mRNA, inhibit translation. Thus, our results indicate that despite the robustness of the decoding process, its tolerance toward the weakening of codon-anticodon interactions is limited. The recognition of the mRNA codon by the tRNA anticodon is crucial for protein synthesis. Here the authors introduce non-standard nucleotides in bacterial and eukaryotic mRNA to reveal the minimal hydrogen bond requirement of codon-anticodon interaction for efficient and accurate translation.